Computational Intelligence International Joint Conference, IJCCI 2016 Porto, Portugal, November 9-11, 2016 Revised Selected Papers - Merelo, Juan Julian; Melício, Fernando; Cadenas, José M.; Dourado, António; Madani, Kurosh; Ruano, António; Filipe, Joaquim (Studies in Computational Intelligence, 2019)
This book gathers revised and extended versions of the best papers presented at the 8th International Joint Conference on Computational Intelligence (IJCCI 2016), which was held in Porto, Portugal from 9 to 11 November 2016. The papers address three main fields of Computational Intelligence, namely: Evolutionary Computation, Fuzzy Computation, and Neural Computation. In addition to highlighting recent advances in these areas, the book offers veteran researchers new and innovative solutions, while also providing a source of information and inspiration for newcomers to the field.